2016
DOI: 10.1093/jxb/erw269
|View full text |Cite
|
Sign up to set email alerts
|

Nineteenth century French rose (Rosasp.) germplasm shows a shift over time from a European to an Asian genetic background

Abstract: HighlightThe impact of breeding on the genetic diversity and structure of roses, during the 19th century in Europe, was studied using a genetic and historical interdisciplinary approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 57 publications
3
50
0
Order By: Relevance
“…Rosa is generally divided into ten sections, four of which (Synstylae, Gallicanae, Indicae and Pimpinellifoliae) have contributed to the gene pool of the domesticated rose (Smulders et al ., ). Rosa hybrida , or the hybrid tea rose, is nowadays the most well‐known and commercially important representative of the genus and has a complex mixture of hybrid perpetuals derived from China rose, Noisettes ( Rosa chinensis ), Bourbons as well as Rosa gallica and Rosa alba , and tea roses ( Rosa × odorata ) in its pedigree (Koning‐Boucoiran et al ., ; Liorzou et al ., ). Given this complexity of origin, it is not surprising that it remains a poorly understood species genetically (Debener and Linde, ).…”
Section: Introductionmentioning
confidence: 97%
“…Rosa is generally divided into ten sections, four of which (Synstylae, Gallicanae, Indicae and Pimpinellifoliae) have contributed to the gene pool of the domesticated rose (Smulders et al ., ). Rosa hybrida , or the hybrid tea rose, is nowadays the most well‐known and commercially important representative of the genus and has a complex mixture of hybrid perpetuals derived from China rose, Noisettes ( Rosa chinensis ), Bourbons as well as Rosa gallica and Rosa alba , and tea roses ( Rosa × odorata ) in its pedigree (Koning‐Boucoiran et al ., ; Liorzou et al ., ). Given this complexity of origin, it is not surprising that it remains a poorly understood species genetically (Debener and Linde, ).…”
Section: Introductionmentioning
confidence: 97%
“…The specificities of the domestication process in perennials are partly due to clonal propagation and long juvenile phases, that both reduce the number of sexual cycles separating domesticated individuals from their wild progenitors (Gaut et al, 2015;Miller & Gross, 2011). Recent studies have corroborated such expectations by documenting the domestication history of several perennial crops, in particular of tree species cultivated for fruit consumption (Besnard et al, 2013(Besnard et al, , 2017Cornille et al, 2012;Decroocq et al, 2016;Delplancke et al, 2013;Gros-Balthazard et al, 2017;Gross & Olsen, 2010;Hazzouri et al, 2015;Wincker, 2013) or ornamental purposes (Iwata, Kato, & Ohno, 2000;Liorzou et al, 2016;Yuan, Cornille, Giraud, Cheng, & Hu, 2014). These studies also revealed that domestication in fruit trees often involved gene flow from multiple wild species in different geographic areas, such as in citrus (Wu et al, 2018), apple (Cornille et al, 2012), olive (Besnard et al, 2017), peach (Yu et al, 2018), banana (Martin et al, 2017) and date palm (Flowers et al, 2019).…”
mentioning
confidence: 99%
“…Rosa is generally divided into ten sections, four of which (Synstylae, Gallicanae, Indicae and Pimpinellifoliae) have contributed to the domesticated rose genepool . Rosa hybrida or the hybrid tea rose is nowadays the most well-known and commercially-important representative of the genus and has a complex mixture of hybrid perpetuals derived from China rose, Noisettes (Rosa chinensis), Bourbons as well as R. gallica and R. alba, and tea roses (R. x odorata) in its pedigree (Koning-Boucoiran et al, 2012;Liorzou et al, 2016). Given this complexity of origin, it is not surprising that it remains a poorly-understood species genetically (Debener and Linde, 2009).…”
Section: Genetic Mapping In Rosementioning
confidence: 99%